Oxidation of Methionine 77 in Calmodulin Alters Mouse Growth and Behavior - Méry Marimoutou; Danielle A. Springer; Chengyu Liu; Geumsoo Kim; Rodney L. Levine (MDPI AG, 2018)
Methionine 77 in calmodulin can be stereospecifically oxidized to methionine sulfoxide by mammalian methionine sulfoxide reductase A. Whether this has in vivo significance is unknown. We therefore created a mutant mouse in which wild type calmodulin-1 was replaced by a calmodulin containing a mimic of methionine sulfoxide at residue 77. Total calmodulin levels were unchanged in the homozygous M77Q mutant, which is viable and fertile. No differences were observed on learning tests, including the Morris water maze and associative learning. Cardiac stress test results were also the same for mutant and wild type mice. However, young male and female mice were 20% smaller than wild type mice, although food intake was normal for their weight. Young M77Q mice were notably more active and exploratory than wild type mice. This behavior difference was objectively documented on the treadmill and open field tests. The mutant mice ran 20% longer on the treadmill than controls and in the open field test, the mutant mice explored more than controls and exhibited reduced anxiety. These phenotypic differences bore a similarity to those observed in mice lacking calcium/calmodulin kinase IIα (CaMKIIα). We then showed that MetO77 calmodulin was less effective in activating CaMKIIα than wild type calmodulin. Thus, characterization of the phenotype of a mouse expressing a constitutively active mimic of calmodulin led to the identification of the first calmodulin target that can be differentially regulated by the oxidation state of Met77. We conclude that reversible oxidation of methionine 77 in calmodulin by MSRA has the potential to regulate cellular function.